Adaptive Laboratory Evolution of Native Torulaspora delbrueckii YCPUC10 With Enhanced Ethanol Resistance and Evaluation in Co-inoculated Fermentation - Catrileo, Daniela; Acuña-Fontecilla, Andrea; Godoy, Liliana (Frontiers in Microbiology, 2020)
Torulaspora delbrueckii is a yeast species typically present in the early stages of the fermentation process. T. delbrueckii positively modifies the aromatic properties of wines. However, its contribution to the final quality of the wine is restricted by its low tolerance to ethanol. T. delbrueckii is capable of fermenting and tolerating an ethanol concentration ranging from 7.4% (v/v) to slightly higher than 9% (v/v). For this reason, it cannot complete fermentation, when alcohol reach levels higher than 12% (v/v), limiting their use in the industry. The objective of this work was to obtain new variants of T. delbrueckii with improved resistance to ethanol through adaptive laboratory evolution. Variants capable of tolerating ethanol levels of 11.5% (v/v) were obtained. These presented improved kinetic parameters, and additionally showed an increase in resistance to SO2 in ethanol compared to the original strain. Co-inoculated fermentations were performed with the original strain (FTd/Sc) and with the evolved strain (FTdF/Sc), in addition to a control fermentation using only Saccharomyces cerevisiae EC1118 (FSc). The results obtained show that FTdF/Sc present higher levels of 2-Ethylhexanol, compared to FTd/Sc and FSc. Furthermore, FTdF/Sc presents higher levels of total alcohols, total aldehydes, total phenolic derivatives, and total sulfur compounds with significant differences with FSc. These results provide a T. delbrueckii YCPUC10-F yeast with higher resistance to ethanol, which can be present throughout the fermentation process and be used in co-inoculated fermentations. This would positively impact the performance of T. delbrueckii by allowing it to be present not only in the early stages of fermentation but to remain until the end of fermentation.